His bundle electrogram in patients with acute myocardial infarction complicated by atrioventricular or intraventricular conduction disturbances. Issue 7 (July 1975) - Harper, R; Hunt, D; Vohra, J; Peter, T; Sloman, G
Abstract : Seventy-two patients with acute myocardial infarction complicated by atrioventricular or bundle-branch block or a combination of both had His bundle electrogram studies performed during their stay in the coronary care unit. In 19 of the 72 patients a repeat His bundle electrogram was performed before discharge from hospital. These studies demonstrated that 30 of the 32 patients with atrioventricular block and narrow QRS complexes had a block above the origin othe His spike (proximal block). Eleven patients in this group had repeat His bundle electrograms performed before discharge and in 3 patients there was evidence of residual atrioventricular nodal dysfunction. Both the hospital and follow-up mortality in this group was low and there was no evidence to suggest that permanent pacing would benefit these patients. Of the 18 patients with bundle-branch block and a normal PR interval, 9 had prolongation of the HV interval, but there was no difference in mortality in patients with normal or prolonged HV intervals. Twenty-two patients with bundle-branch block also developed atrioventricular block. In 5 of these patients the site of the AV block was proximal and in 14 it was distal, while 3 patients had both proximal and distal block. The hospital mortality in those patients who progressed to second- or third-degree atrioventricular block was considerably higher than in those patients who remained in first-degree atrioventricular block.